Transcranial direct current stimulation of 3 cortical targets is no more effective than placebo as treatment for fibromyalgia: a double-blind sham-controlled clinical trial - Samartin-Veiga, Noelia (2022)
Transcranial direct current stimulation (tDCS) over the primary motor cortex (M1) and the dorsolateral prefrontal cortex seem to improve pain and other symptoms of fibromyalgia (FM), although the evidence on the effectiveness of tDCS and the optimal stimulation target is not robust enough. Our main objective was to establish the optimal area of stimulation, comparing the 2 classical targets and a novel pain-related area, the operculo-insular cortex, in a sham-controlled trial. Using a double-blind design, we randomly assigned 130 women with FM to 4 treatment groups (M1, dorsolateral prefrontal cortex, operculo-insular cortex, and sham), each receiving fifteen 20-minute sessions of 2 mA anodal tDCS over the left hemisphere. Our primary outcome was pain intensity. The secondary outcomes were the other core symptoms of FM (fatigue, mood, cognitive and sleep disorders, and hyperalgesia measured by the pressure pain threshold). We performed the assessment at 3 time points (before, immediately after treatment, and at 6 months follow-up). The linear mixed-model analysis of variances showed significant treatment effects across time for clinical pain and for fatigue, cognitive and sleep disturbances, and experimental pain, irrespective of the group. In mood, the 3 active tDCS groups showed a significantly larger improvement in anxiety and depression than sham. Our findings provide evidence of a placebo effect, support the use of tDCS for the treatment of affective symptoms, and challenge the effectiveness of tDCS as treatment of FM.